Barley (Hordeum vulgare L.) yield with normal and coated urea in Pintag, Quito, Ecuador. - Lema-Aguirre, Andrea C.; Basantes-Morales, Emilio R.; Pantoja-Guamán, José L. (Agronomía Mesoamericana, 2016)
The objective of this investigation was to evaluate the response of barley production to nitrogenized fertilization (NF) and its impact on the protein content of the grain and the availability of nutrients on the soil. The study was carried out in two sites in Hacienda Valencia, in Pintag, Quito, Ecuador, between March 2014 and February 2015. A variety of INIAP Cañicapa 2003 was used, and the NF was done with normal urea and polymerized (urea + tiophosphate of N-nbutiltriamida). An experimental design of randomized full blocks in four repetitions of divided lots [the urea (normal and polymerized) was used in the main lot and the NF (0, 30, 60, 90, 120, y 150 kg N/ha) in the sub-lot]. 110 kg/ha of seed was used; 50% of the NF was applied three weeks after planting (broadcast) and 50% eight weeks after. The type of urea did not affect the production (p>0,10), although the average was different between two sites (4,33 y 2,08 t/ha for sites 1 and 2, respectively). Excess of rain could have limit the effect on the urea type. On average a cuadratic response to NF was obtined, with an optimum dose of N (DON) of 90 kg N/ha and a production of 3,41 t/ ha. This DON was similar to the dose of N recomended for barley in Ecuador. The NF augmented the protein content up to 14,50% (p<0,01) and acidified the ground, because the urea nitrification produces H+.